2020
DOI: 10.1007/s40200-020-00672-4
|View full text |Cite
|
Sign up to set email alerts
|

Maternal circulating levels of Adipocytokines and insulin resistance as predictors of gestational diabetes mellitus: preliminary findings of a longitudinal descriptive study

Abstract: Purpose The present study aimed to assess the role of adipocytokines as predictive markers of gestational diabetes mellitus (GDM). We undertook this study to explore the association of adiponectin, resistin, interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-alpha) and insulin resistance in the development of GDM. Methods This longitudinal descriptive study was done in the Medical College Hospital, involving the departments of Biochemistry and Gynecology. The study subjects were pregnant women with norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Adiponectin circulating levels increase during the first and second trimesters of normal pregnancy and later decrease post-partum [ 178 ]. Unlike leptin, low levels of adiponectin were found in maternal GDM serum compared to women with normal glucose tolerance [ 179 , 180 ]. It has been proposed that this decrease in serum adiponectin levels may serve as an early predictive factor for GDM development.…”
Section: Hyperglycemia-induced Metainflammation In Gdm Alters Placental Immune Cells Population Favoring An Inflammatory Cytokine Signatumentioning
confidence: 99%
“…Adiponectin circulating levels increase during the first and second trimesters of normal pregnancy and later decrease post-partum [ 178 ]. Unlike leptin, low levels of adiponectin were found in maternal GDM serum compared to women with normal glucose tolerance [ 179 , 180 ]. It has been proposed that this decrease in serum adiponectin levels may serve as an early predictive factor for GDM development.…”
Section: Hyperglycemia-induced Metainflammation In Gdm Alters Placental Immune Cells Population Favoring An Inflammatory Cytokine Signatumentioning
confidence: 99%
“…Thereafter, Jin et al [30] reported that the dynamic change in fetuin-A levels was associated with the changes in IR and β-cell function from the 1st to the 2nd trimester, and was associated with an increased risk of the development of GDM. Also, Ramachandrayya et al [31] found the levels of resistin, IL-6 and TNF-α were higher at 24 than at 12 GW in both healthy pregnant and GDM women with significantly higher levels in women with GDM than women with healthy pregnancy. Recently, Eroğlu et al [32] detected higher serum levels of afamin in women who developed GDM than control women and Al-Musharaf et al [33] detected significantly and progressively increasing serum levels of TNF-α, leptin and resistin from the 1st to the 2nd trimester in GDM women than in no-GDM women and considered these disturbed levels of adipocytokines during the course of pregnancy may play a role in pathogenesis of GDM.…”
Section: Discussionmentioning
confidence: 96%
“…The adipose tissue secretes multiple adipokines which are mostly pro‐inflammatory 59 and are associated with various metabolic diseases, such as GDM, type 2 diabetes, and obesity 60 . Adiponectins have been shown to be negatively associated with GDM 60 , whereas leptin was linked with a higher risk of GDM 61 .…”
Section: Circulating Lipid Profiles and Gdmmentioning
confidence: 99%